2021
DOI: 10.25259/ijdvl_713_20
|View full text |Cite
|
Sign up to set email alerts
|

Atrophic pigmented dermatofibrosarcoma protuberans misdiagnosed as hyperpigmentation

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution-Non Commercial-Share Alike 4.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as the author is credited and the new creations are licensed under the identical terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Moreover, years after the initial diagnosis, a minority of nearly 6% can invade distant organs such as the lungs [16]. However, one study reported 15% lung metastasis in DFSP cases in correlation with other forms of high-grade sarcomas [6,13,[17][18][19]. Age and gender are not risk factors for DFSP and its recurrence.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, years after the initial diagnosis, a minority of nearly 6% can invade distant organs such as the lungs [16]. However, one study reported 15% lung metastasis in DFSP cases in correlation with other forms of high-grade sarcomas [6,13,[17][18][19]. Age and gender are not risk factors for DFSP and its recurrence.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…4 Sections of ill-defined mesenchymal neoplasm involving papillary and reticular dermis sign of malignancy in DFSP lesions. It is advised that such patients should be referred to a cancer center with staff members experienced in cases of lesions with suspected sarcoma, for the purpose not only of preoperative microscopic study of the lesions, but also their treatment [8,18,20]. As the DFSP grows to late stages, it can be ulcerative, painful, and bleeding, in contrast to a low-grade lesion [16].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…A 2020 case out of Bejing, China, by Lin et al, documented a case of DFSP misdiagnosed for 10 years as post-inflammatory hyperpigmentation [ 12 ]. The patient was a 33-year-old female with a 1.6 x 1.3 cm erythematous-to-bluish, ill-defined, depressed plaque on the left upper back.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed diagnosis and misdiagnosis are common. 5/8 cases of atrophic pigmented DFSP were misdiagnosed as benign lesions, including nevus of Ota, postinflammatory hyperpigmentation, hemangioma, and lipoatrophy ( 20 , 55 , 61 ). A high index of suspicion and a broad differential diagnosis by dermatologists is necessary.…”
Section: Discussionmentioning
confidence: 99%